2017
DOI: 10.3390/sym9100212
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach Based on Time Cluster for Activity Recognition of Daily Living in Smart Homes

Abstract: Abstract:With the trend of the increasing ageing population, more elderly people often encounter some problems in their daily lives. To enable these people to have more carefree lives, smart homes are designed to assist elderly people by recognizing their daily activities. Although different models and algorithms that use temporal and spatial features for activity recognition have been proposed, the rigid representations of these features damage the accuracy of activity recognition. In this paper, a two-stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Activity recognition in smart homes can be divided into knowledge-driven and data-driven [13][14][15]. For knowledgedriven approach, knowledge is generated from field experts.…”
Section: Related Workmentioning
confidence: 99%
“…Activity recognition in smart homes can be divided into knowledge-driven and data-driven [13][14][15]. For knowledgedriven approach, knowledge is generated from field experts.…”
Section: Related Workmentioning
confidence: 99%
“…Two papers on smart home are included as follows: (1) "A novel approach based on time clusters for activity recognition of daily living in smart homes", by Liu et al [48]; and (2) "IoT-based image recognition systems for smart home-delivered meal services", by Tseng et al [49].…”
Section: Smart Homementioning
confidence: 99%
“…In Stage 1, the practical sensing data can be clustered in accordance with temporal features; in Stage 2, some classification methods (e.g., naive Bayesian classifier, k-nearest neighbors, decision tree, and random forest) were applied to analyze the practical sensing data of each cluster, and to a generate classification model for each cluster. In experimental environments, the two open datasets from the "single-resident apartment data" provided by Washington State University were collected to evaluate the proposed method, and the results showed that the average classification accuracy of the proposed two-stage time clustering method is higher than the one-stage method without time clustering [48].…”
Section: Smart Homementioning
confidence: 99%
“…Activity recognition is considered an important area of research, particularly in the field of healthcare services [1]. The significance of this area is mainly due to the provision of support and assistance for elderly, disabled and cognitively impaired people [2]. Furthermore, activity recognition has become a primary indicator to measure physical and mental health of elderly individuals based on their ability to perform basic activities such as bathing, eating and cooking [3].…”
Section: Introductionmentioning
confidence: 99%